Effects of blue and red LED lights on rubisco activase gene expression, CO2 fixation efficiency and plant morphology of Gerbera jamesonii - Khac Hung, Nguyen; Thi Gam, Do; Thi Huyen Trang, Hoang; Hoang Ha, Chu; Tien Phat, Do; Bich Ngoc, Pham (Vietnam Journal of Biotechnology, 2022)
Light quality is known to affects numerous plants’ physiological and metabolic processes during development period, including photosynthesis and morphogenesis. Light properties such as light wavelength has been optimized for several cultivated crops. In this study, the effects of LED light wavelengths blue and red on both photosynthetic performance and morphology of Gerbera jamesonii plantlets was investigated. The results showed the photosynthesis efficiency via the photo-pigment system and mediated regulation of rubisco activase encoding gene (RCA) mechanism was significantly enhanced by blue light. The expression of RCA was approximatly 2.7 times higher than those under red light. In contrast, chlorophyll contents, CO2 assimilation, total carbohydrate and RCA expression was reduced under red wavelength. However, both single-wavelengths caused a dramatically negative impact on G. jamesonii. Total chlorophyll/carotenoid value or higher carotenoid contents was lower under blue light; fragile petioles and drawrfism morphology was occurred under red and blue LED, respectively. The combination of blue and red light in the lighting spectrum significantly improved the limitations of single-wavelength. The supplement of blue light under red light background (at blue LED and red LED ratio = 1:4) improved plant photosynthesis while maintained the normal morphology of plants, although the expression of RCA and net photosynthesis of plants in BR LED was lower than in the control. Our results obviously provide the scientific evidences for requirement of LED light in micropropagation or canopy culture of G. jamesonii.